The role of language in nation-building process - Anna Grzywacz (UPT P2M Politeknik Negeri Malang, 2012)
Language function can be classified into four categories: cognitive (related to learners’ intellectual development), instrumental (related to the use of language for material purposes), integrative (related to group membership) and cultural (related to cultural appreciation and understanding). In addition to that, language may be also used as a political and social element in the process of building, unification and maintaining of a nation and as an essential element of national identity. This article discusses cases in relation to the social-political related function of language. It shows interesting aspects of three different languages in serving this function. The first is Indonesian language, a neutral language, which was adopted in Indonesia primarily to unite the society in a newly built nation. The second is the Hebrew language, which has been restored to be an initial reference point for the Jewish people, and became an official language of Israel, and become a key element of national identity. The last one is the Polish language, which is an example of a language that has survived despite the absence of the Polish state and also became an essential element of connecting the Polish society.